Inflation and the Savings Rate - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 1982)
This paper examines two explanations of the observed positive relationship between inflation rates and saving rates in Canada and the United States. Several models are estimated using quarterly time series data from both countries, and the best of these are subjected to a variety of tests. One of the two explanations appears broadly consistent with the data. The observed relationship arises primarily because, in times of inflation, measured income and measured savings overstate the corresponding real and perceived quantities.
Keywords: E21; 330; inflation; savings; inflation; savings; income; wealth; mismeasurement